Achieving high circularly polarized luminescence with push–pull helicenic systems: from rationalized design to top-emission CP-OLED applications. Issue 15 (12th March 2021) - Dhbaibi, Kais; Abella, Laura; Meunier-Della-Gatta, Sylvia; Roisnel, Thierry; Vanthuyne, Nicolas; Jamoussi, Bassem; Pieters, Grégory; Racine, Benoît; Quesnel, Etienne; Autschbach, Jochen; Crassous, Jeanne; Favereau, Ludovic
Abstract : A CPL intensity of up to 3 × 10 −2 is achieved in π-extended 6-helicene derivatives, owing to an intense helicene-mediated exciton coupling. Corresponding top-emission CP-OLEDs afforded a promising g El of around 8 × 10 −3 . Abstract : While the development of chiral molecules displaying circularly polarized luminescence (CPL) has received considerable attention, the corresponding CPL intensity, g lum, hardly exceeds 10 −2 at the molecular level owing to the difficulty in optimizing the key parameters governing such a luminescence process. To address this challenge, we report here the synthesis and chiroptical properties of a new family of π-helical push–pull systems based on carbo[6]helicene, where the latter acts as either a chiral electron acceptor or a donor unit. This comprehensive experimental and theoretical investigation shows that the magnitude and relative orientation of the electric ( μe ) and magnetic (μ m ) dipole transition moments can be tuned efficiently with regard to the molecular chiroptical properties, which results in high g lum values, i.e. up to 3–4 × 10 −2 . Our investigations revealed that the optimized mutual orientation of the electric and magnetic dipoles in the excited state is a crucial parameter to achieve intense helicene-mediated exciton coupling, which is a major contributor to the obtained strong CPL. Finally, top-emission CP-OLEDs were fabricated through vapor deposition, which afforded a promising g El of around 8 × 10 −3 . These results bring about further molecular design guidelines to reach high CPL intensity and offer new insights into the development of innovative CP-OLED architectures.